2022
DOI: 10.31098/orcadev.v1i1.867
|View full text |Cite
|
Sign up to set email alerts
|

On The Employee Performance In The Bekasi Region

Abstract: Human resources play a critical role in a company's development and achievement of its objectives. Workers' quality and morale suffer as a result of managers' failure to pay attention to their requirements and expectations. Human resource management and development are expected of organizations. The purpose of this study is to assess and analyze the impact of rewards and punishment on employee performance. The approach of purposeful sampling is used to choose samples from a number of organizations that match t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…Productivity encompasses work effectiveness and quality (meeting technical and customer specifications). In addition to the former, managers' inability to attend to workers' needs and expectations has a detrimental impact on both the quality of work produced and the overall morale of the workforce (Nursiti et al, 2022). Productivity measurement includes work output and resource utilization (Brynjolfsson et al, 2020;Harris, 1994;Ruch & Hershauer, 1974).…”
Section: Productivity and Its Variablesmentioning
confidence: 99%
“…Productivity encompasses work effectiveness and quality (meeting technical and customer specifications). In addition to the former, managers' inability to attend to workers' needs and expectations has a detrimental impact on both the quality of work produced and the overall morale of the workforce (Nursiti et al, 2022). Productivity measurement includes work output and resource utilization (Brynjolfsson et al, 2020;Harris, 1994;Ruch & Hershauer, 1974).…”
Section: Productivity and Its Variablesmentioning
confidence: 99%
“…Employee performance is well researched in the field of human resources because it plays an integral role in developing and achieving the goals of an organization (Nursiti et al, 2022). It refers to how employees fulfil their duties, accomplish assigned tasks, and behave as a member of the organization.…”
Section: Research Papermentioning
confidence: 99%
“…Nursiti et al investigated the influence of punishment and reward in a statistical study. Their statistical results suggested that punishment would affect the performance of guilty employees similarly to the way that rewards affected it [61].…”
Section: Examination Of Mechanism Characteristicsmentioning
confidence: 99%